Leveraging Artificial Intelligence for Advancements in the Pharmaceutical Field: A Comprehensive Review - Hesham, Mostafa (My University, 2023)
The pharmaceutical industry has witnessed a paradigm shift with the integration of artificial intelligence (AI) into various aspects of drug discovery, development, and healthcare delivery. This paper provides a comprehensive review of the impact of AI in the pharmaceutical field, highlighting its contributions, challenges, and prospects. We explore AI applications in drug discovery, clinical trials, personalized medicine, and healthcare management, emphasizing the potential benefits and ethical considerations associated with this transformative technology.
Keywords: AI; Computer vision; pharmaceutical